BIOFILTER MANUFACTURE OF AZADIRACHTA INDICA LEAF POWDER AND ITS EFFECTIVENESS IN CAPTURING FREE RADICALS OF CIGARETTE SMOKE - Agus Mulyono (Spektra: Jurnal Fisika dan Aplikasinya, 2022)
Free radicals from cigarette smoke are a dangerous part that must be found to counteract. This research aims to make a composite biofilter made from Azadirachta Indica to ward off/capture free radicals from cigarette smoke. This biofilter is made with Azadirachta Indica leaf powder added to polyethylene glycol as the matrix. The biofilter was then seen for its physical characteristics; the density and porosity were tested using SEM. Furthermore, a biofilter membrane is used to filter cigarette smoke. Cigarette smoke that passes through the biofilter is then analyzed using ESR for its free radical content. The results showed that the biofilter made from Azadirachta Indica leaves could absorb several types of suspected free radicals in cigarette smoke. Biofilters using PEG as a matrix with a mass of 0.9 and 1gr were the most effective in absorbing the suspected types of free radicals. SEM test showed an average pore size of 2-3 µm for a mass of 1gr with PEG as the matrix.